DYSTOCIA DUE TO LATERAL DEVIATION OF HEAD AND NECK IN A PRIMIPAROUS MURRAH BUFFALO - KUMAR, SUDHIR; KUMAR, SHARAD; SHARMA, UTSAV; KUSHWAHA, R B; KUMAR, SUDERSHAN; BHARDWAJ, ANAVIL (The Indian Journal of Animal Reproduction, 2023)
Successful caesarean delivery of foetus in dystocia due to lateral deviation of the head and neck in a primiparous Murrah buffalo has been reported.